Economic policy and the adjustment problem - Banks, Gary.; Tumlir, Jan. (London : Gower for the Trade Policy Research Centre, 1986)
The purpose of this Thames essay is to clarify thinking on the adjustment process of the market and the role of economic policy.
Includes bibliographical references.
ne 10/07/2018
Loans
Keywords: Trade adjustment assistance; Economic policy; Protectionism